2018
DOI: 10.1038/s41419-018-1182-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 promotes EGF-induced pancreatic cancer cell proliferation by targeting Spry2

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant cancer that lacks effective targets for therapy. Alteration of epidermal growth factor (EGF) expression has been recognized as an essential molecular event in pancreatic carcinogenesis. Accumulating studies have demonstrated that miRNAs play critical roles in EGF signaling regulation, tumor initiation, cell proliferation and apoptosis. Here, we demonstrated that miR-21 expression was induced by EGF in pancreatic cancer cells. miR-21 promoted EGF-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 43 publications
0
55
0
Order By: Relevance
“…Dual‐specificity tyrosine phosphorylation‐regulated kinase 1A, which is highly expressed in pancreatic ductal adenocarcinoma, stabilizes c‐Met through Sprouty2 phosphorylation, thereby resulting in the promotion of tumor growth . In pancreatic cancer cells, miR‐21 targets Sprouty2 for promoting EGF‐induced cell proliferation . Sprouty4 does not affect β‐cell carcinogenesis in mice, although it regulates endocrine pancreas development …”
Section: Roles Of Sprouty/spred During Tumorigenesis and Metastasismentioning
confidence: 99%
“…Dual‐specificity tyrosine phosphorylation‐regulated kinase 1A, which is highly expressed in pancreatic ductal adenocarcinoma, stabilizes c‐Met through Sprouty2 phosphorylation, thereby resulting in the promotion of tumor growth . In pancreatic cancer cells, miR‐21 targets Sprouty2 for promoting EGF‐induced cell proliferation . Sprouty4 does not affect β‐cell carcinogenesis in mice, although it regulates endocrine pancreas development …”
Section: Roles Of Sprouty/spred During Tumorigenesis and Metastasismentioning
confidence: 99%
“…Furthermore, miR-21 is involved in the MAPK signalling pathway, which is important for the progression of pancreatic intraepithelial neoplasia (PanIN [ 45 ]). Overexpression of miR-21 has been shown to moderate cell proliferation and apoptosis of PDAC cells through the inhibition of both MAPK/ERK and PI3K/AKT signalling pathways [ 46 ]. Expression of miR-21 is also associated with the TGF-β signalling pathway, which is dysregulated in 80% of PDAC cases [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 Amounts of evidence showed that miRNAs played important roles in cancers, including tumorigenesis, cell signaling transduction, cell proliferation, apoptosis, tumor invasion and metastasis. [29][30][31] Recently, a novel regulatory mechanism, called ceRNA hypothesis, has been proposed, wherein specific RNAs can impair miRNAs activity through competing with shared miRNAs response elements (MREs), thereby upregulating miRNAs target gene expression. 32 For example, circMLLT10 promotes gastric cancer cell growth and metastasis via sponging miR-509-3-5p to promote GINS4 expression.…”
Section: Introductionmentioning
confidence: 99%